(untitled) ("Journal "U". Economy. Management. Finance.", 2016)
The paper studies the possibilities of development of tourist logistical service and its priority areas. The article summarizes the most relevant areas of logistic service, gives structure of main stages of the logistics service system, proposes quantitative and graphical tools provided to assess the level of logistic service. In the result of the work key criteria for assessing the quality are identified, and recommendations for optimizing the amount of logistics services are proposed.